Insights into fungal diversity of a shallow-water hydrothermal vent field at Kueishan Island, Taiwan by culture-based and metabarcoding analyses. - Ka-Lai Pang; Sheng-Yu Guo; I-An Chen; Gäetan Burgaud; Zhu-Hua Luo; Hans U Dahms; Jiang-Shiou Hwang; Yi-Li Lin; Jian-Shun Huang; Tsz-Wai Ho; Ling-Ming Tsang; Michael Wai-Lun Chiang; et al. (PLoS ONE)
This paper reports the diversity of fungi associated with substrates collected at a shallow hydrothermal vent field at Kueishan Island, Taiwan, using both culture-based and metabarcoding methods. Culture of fungi from yellow sediment (with visible sulfur granules), black sediment (no visible sulfur granules), the vent crab Xenograpsus testudinatus, seawater and, animal egg samples resulted in a total of 94 isolates. Species identification based on the internal transcribed spacer regions of the rDNA revealed that the yellow sediment samples had the highest species richness with 25 species, followed by the black sediment (23) and the crab (13). The Ascomycota was dominant over the Basidiomycota; the dominant orders were Agaricales, Capnodiales, Eurotiales, Hypocreales, Pleosporales, Polyporales and Xylariales. Hortaea werneckii was the only common fungus isolated from the crab, seawater, yellow and black sediment samples. The metabarcoding analysis amplifying a small fragment of the rDNA (from 18S to 5.8S) recovered 7-27 species from the black sediment and 12-27 species from the yellow sediment samples and all species belonged to the Ascomycota and the Basidiomycota. In the yellow sediments, the dominant order was Pleosporales and this order was also dominant in the black sediment together with Sporidiobolales. Based on the results from both methods, 54 and 49 species were found in the black and yellow sediments, respectively. Overall, a higher proportion of Ascomycota (~70%) over Basidiomycota was recovered in the yellow sediment and the two phyla were equally abundant in the black sediment. The top five dominant fungal orders in descending order based on species richness were Pleosporales>Eurotiales>Polyporales>Hypocreales>Capnodiales in the black sediment samples, and Polyporales>Pleosporales>Eurotiales>Capnodiales>Hypocreales in the yellow sediment samples. This study is the first to observe a high diversity of fungi associated with various substrates at a marine shallow water hydrothermal vent ecosystem. While some fungi found in this study were terrestrial species and their airborne spores might have been deposited into the marine sediment, several pathogenic fungi of animals, including Acremonium spp., Aspergillus spp., Fusarium spp., Malassezia spp., Hortaea werneckii, Parengyodontium album, and Westerdykella dispersa, were recovered suggesting that these fungi may be able to cause diseases of marine animals.